Smoking status and copd awareness of teachers in Sanliurfa (Annals of Medical Research, 2023)
Aim: This study aims to investigate the smoking status of teachers, the relationship between smoking and COPD, and teachers' awareness of COPD.Materials and Methods: 504 teachers participated in this cross-sectional study. The data was obtained through an online questionnaire utilizing a 22-question form designed by the researchers.Results: The mean age of the participants was 38.67 ± 7.70 years, 47.8% of them were female, and 81.5% worked in public schools. 27.8% of teachers reported smoking. 24.4% of teachers reported living with a COPD patient, with 86.5% citing smoking as the major risk factor for COPD.  88.3% of participants indicated that avoiding tobacco products is crucial in preventing COPD. The majority of participants (92.7%) provided the correct response when asked about the symptoms of COPD. While 67.7% responded that PFT is used for diagnosis, 50.6% reported that it is a treatable disease, and 25.2% reported that inhaler medicines are used for treatment. There was a statistically significant distinction between the frequency of hearing about COPD and the specialties of the teachers. It was shown that 91.1% of smokers were aware of COPD, however, no statistical correlation was found between smoking and awareness.Conclusion: This study revealed that the prevalence of smoking among teachers in Sanliurfa was lower than previously reported in the literature. The level of awareness that COPD is a lung disease was found to be higher than in previous studies of a similar sort. It was established that awareness of the risk factors for COPD, its symptoms, preventive strategies, and the fact that COPD is a treatable disease was high. We believe that this awareness will play a crucial role in protecting students from smoking and various smoking-related diseases, such as COPD.
Keywords: Teacher; Smoking; COPD; Awareness